Etnomatematika pada permainan tradisional lompek kodok bengkulu - Ananda, Wella; Risnanosanti, Risnanosanti; Syofiana, Mardiah (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
Ethnomathematics combines elements of mathematics with the culture and traditions of society. Culture is a complete and comprehensive unity that applies to society, while mathematics is a science that society uses to solve everyday problems. The aim of this research is to find mathematical patterns contained in the traditional game Lompek Kodok and to find out how players use mathematics naturally in the game strategy. Data collected through qualitative research methods, and interviews with elders and trusted people, direct game observation, and analysis of game rules. The first stage of research involves determining the topic and discussion that will be researched, then determining the area that will be used as the search location. After that, design and organize the time needed to complete data collection using interviews and observations. Then record the results of the interview and document them. The next step is data analysis by processing the data obtained and describing the ethnomathematics in the traditional Bengkulu lompek kodok game. It is hoped that the results of this research will provide new insights into how mathematical concepts can be used in local culture through ethnomathematics.